A de novo c.1509dupA:p.R503fs mutation of FUS: report of a girl with sporadic juvenile amyotrophic lateral sclerosis. Issue 7 (1st October 2020) - Chen, Li; Li, Junmin; Lu, Hong; Liu, Yanru
Abstract: Juvenile amyotrophic lateral sclerosis (JALS) is a rare and severe form of ALS. The development of sequencing methods has resulted in increased reports of JALS cases in recent years, this study, we identified a novel heterozygous mutation in exon 14, c.1509dupA:p.R503fs, of the RNA-binding protein fused in sarcoma (FUS) in a 17-year-old female patient with sporadic JALS who experienced rapid progression of muscular atrophy and died of respiratory failure 15 months after onset. Early onset, progressive muscular atrophy and weakness of the limbs with absence of intellectual impairment were the characteristics of this patient.